Protocol: The impact of integrated thematic instruction model on primary and secondary school students compared to standard teaching: A protocol of systematic review - Klára Barancová; Jiří Kantor; Martina Fasnerová; Zuzana Svobodová; Miloslav Klugar (Campbell Systematic Reviews)
Abstract This is the protocol for a Campbell systematic review. The objectives are as follows. This systematic review will examine the impact of the Integrated Thematic Instruction (ITI) on academic attainment and other possible outcomes of primary and secondary school students compared to standard teaching. We will seek to answer the following research question: What impact does the ITI/HET teaching has on academic attainment and other possible outcomes of primary and secondary school students compared to standard teaching?